(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: The human vermiform appendix is usually recognized as a secondary lymphoid organ. Vermiform appendix performs functions related with gastrointestinal tract. The main function of it is immunological. Secretory immunoglobulins produced by gut associated lymphoid tissue (GALT) act as an effective barrier. Vermiform appendix has surgical importance too. Appendicitis is the most common clinical condition. An appropriate anatomical knowledge about vermiform appendix is important for surgeons, pathologists and other physicians for proper diagnosis and management of diseased appendix. Materials and Method: A cross sectional descriptive type of study was carried out in the department of Anatomy, Sir Salimullah Medical College on sixty (60) human cadaveric vermiform appendix, age ranging from 0 to 65 years. The collected samples were divided into five age groups such as group A (0-20 years) group B (21-30 years), group C (31-40 years), group D (41-50 years and group E (51 years and above). Fresh specimens were collected from the morgue of Sir Salimullah Medical College and Dhaka Medical College, Dhaka. The present study was conducted to measure the diameter of vermiform appendix. Result: Diameter of vermiform increased upto 50 years of age then decreases and when compared among different age groups were found to be highly significant in the group A vs C, D, E and group B vs D Bangladesh J. Anat. 2014; 12(2) : 62-64